Becoming Madam Secretary - Dray, Stephanie (New York : Berkley, 2024)
"Raised on tales of her revolutionary ancestors, Frances Perkins arrives in New York City at the turn of the century, armed with her trusty parasol and an unyielding determination to make a difference. When she's not working with children in the crowded tenements in Hell's Kitchen, Frances throws herself into the social scene in Greenwich Village, befriending an eclectic group of politicians, artists, and activists, including the millionaire socialite Mary Harriman Rumsey, the flirtatious budding author Sinclair Lewis, and the brilliant but troubled reformer Paul Wilson, with whom she falls deeply in love. But when Frances meets a young lawyer named Franklin Delano Roosevelt at a tea dance, sparks fly in all the wrong directions. She thinks he's a rich, arrogant dilettante who gets by on a handsome face and a famous name. He thinks she's a priggish bluestocking and insufferable do-gooder. Neither knows it yet, but over the next twenty years, they will form a historic partnership that will carry them both to the White House. Frances is destined to rise in a political world dominated by men, facing down the Great Depression as FDR's most trusted lieutenant-even as she struggles to balance the demands of a public career with marriage and motherhood. And when vicious political attacks mount and personal tragedies threaten to derail her ambitions, she must decide what she's willing to do-and what she's willing to sacrifice-to save a nation"--.
new book 2024 spring.
Keywords: Perkins, Frances, -- 1880-1965 -- Fiction; Women -- Political activity -- United States -- Fiction; Women cabinet officers -- United States -- Fiction; Historical fiction; Biographical fiction; United States; Political activity; Novels; Historical fiction; Biographical fiction